2017
DOI: 10.1097/igc.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in the Management of Vulvar Carcinoma an Evidence-Based Insight

Abstract: Sentinel lymph node biopsy-guided management seems to be safe when restricted to International Federation of Gynecology and Obstetrics IB to II cases where tumors are unifocal, less than 4 cm in size, and when there is no evidence of lymph node metastasis on clinical/radiological assessment. This reduces operative morbidity in this cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
1
19
0
2
Order By: Relevance
“…The obtained findings are consistent with those of De Cicco et al and Sliutz et al, who reported a 100% detection rate using Technetium-99-m-labeled nanocolloid, with or without blue dye [11,12]. Additionally a meta-analysis performed by Brincat et al confirmed the safety and feasibility of SLN biopsy in vulvar cancer [13].…”
Section: Discussionsupporting
confidence: 89%
“…The obtained findings are consistent with those of De Cicco et al and Sliutz et al, who reported a 100% detection rate using Technetium-99-m-labeled nanocolloid, with or without blue dye [11,12]. Additionally a meta-analysis performed by Brincat et al confirmed the safety and feasibility of SLN biopsy in vulvar cancer [13].…”
Section: Discussionsupporting
confidence: 89%
“…Currently, there are corresponding recommendations for patients who are eligible for SLNB. Patients with tumors that are unifocal, less than <4 cm in diameter, and with no evidence of lymph node involvement by preoperative assessment, are eligible for SLNB 35 , while patients with multifocal disease, clinically suspicious groin nodes, or a tumor located in the midline are unsuitable 13 , 14 , 24 . In addition, patients who have undergone preoperative radiotherapy/chemotherapy should probably be excluded because damage to the lymph vessels may affect the SLNB procedure 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination of the sentinel lymph node is representative for all other lymph nodes in the area, and histologically, a negative sentinel lymph node means the absence of metastases in subsequent lymph nodes. [16][17][18][19] The sentinel lymph node is marked in two ways, with a nanocolloid bound to 99mTc (Technetium) and with a patent blue. This method is the most reliable, as the sentinel lymph node is found in 97.7% of cases.…”
Section: Surgical Treatmentmentioning
confidence: 99%